Fatores de risco de lesões não intencionais em ambiente doméstico/familiar em crianças - Ramos, Ana Lúcia Caeiro (2014)
Unintentional injuries in children in the context of home and family are the most common cause of death in many countries around the world, including Portugal, showing the need for study and intervention regarding this problem. The aim of this article is to identify the risk factors of unintentional injury in the home/family context in children aged up to 4 years, as described in the literature. The research was conducted in march 2011 and the studies were selected using the PI[C]OS methodology, according to the pre-defined criteria. 32 articles were identified, most with a quantitative approach. Analysis of the articles highlighted several risk factors, in different dimensions and action levels, which matched the multi-faceted nature of the problem. According to the results of the studies, risk factors are related to the child´s characteristics, as well as to the characteristics of the family to which the child belongs. The domestic/family environment and risk behaviors adopted by the family also formed part of the study results. Knowledge of unintentional injury risk factors in childhood is a fruitful basis for future studies, enabling objective interventions adapted to the child/family and taking the risk factors into account.